Answer:
The answer is: y = 7/6x + 3/2
Explanation:
Given the points: (-3, -2) and (3, 5), use the equation for slope:
m = (y - y1)/(x - x1)
m = (-2 - 5)/(-3 - 3)
m = -7 / -6 = 7/6
Then use the point slope form of a line, substituting in the slope and using point (-3, -2):
y - y1 = m(x - x1)
y - (-2) = m(x - (-3))
y + 2 = 7/6x + 21/6
y = 7/6x + 21/6 - 2
y = 7/6x + 21/6 - 12/6
y = 7/6x + 9/6
y = 7/6x + 3/2
Proof using the point (3, 5)
f(3) = 7/6(3) + 3/2
= 21/6 + 3/2
= 21/6 + 9/6
= 30/6 = 5, giving the point (3, 5)
Hope this helps! Have an Awesome day!! :-)